Purification of biodiesel products from transesterification process using ion-exchange resin - Muhammed Abdul Mun'im Mohammad Zaki (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
Biodiesel based on crude palm oil (CPO) is gaining attention as a replacement for current fossil fuels due to high production of CPO locally in Malaysia other government influence on findings solution for global problems regarding to the usage of petrodiesel. As a result, CPO is claimed to be a highly potential feedstock for food origin biodiesel. An acid catalyzed esterification proces using sulphuric acid (H2SO4) was carried out to evaluate te low content of free fatty acids (FFA) in the treated CPO with the effect of other parameters such as methanol to oil molar ratio (6:1) , reaction temperature (40-80'C)reaction time (30-120 minutes) and stirring speed (600 rpm) using PORIM method. The result showed that the FFA of CPO was reduced from 4.24 % to less than 1.0% FFA using 1.0 % wt/wt of H2p2sSOp4s.